Implementation of Active Learning Strategies in Improving Elementary School Students' Learning Engagement: A Literature Review - Amelia Tasya (PT. Anagata Sembagi Education, 2024)
Student learning engagement is one of the main indicators of the success of the educational process at the elementary school level. However, low levels of active student participation in learning activities remain a common problem. This study aims to comprehensively examine the effectiveness of implementing active learning strategies in increasing elementary school students' learning engagement through a literature review method. The approach used was descriptive qualitative, analyzing various scientific sources published in the last five years. The study results indicate that active learning strategies, such as Project-Based Learning, Problem-Based Learning, and Cooperative Learning, consistently contribute positively to students' cognitive, affective, and behavioral engagement. These approaches have also proven effective in developing 21st-century skills and encouraging the development of independent learners. However, implementation challenges such as limited resources, lack of teacher training, and unequal access to education remain major obstacles. Therefore, strengthening teacher capacity, sustainable policy support, and collaboration among stakeholders are needed to optimize the implementation of active learning strategies. This study is expected to serve as a theoretical and practical reference for the development of learning innovations at the elementary school level.